Kinematic analysis of line-out throwing in elite international rugby union - Sayers, M. G. L. (Journal of Sports Science & Medicine, 2011)
The rugby union line-out is a key aspect of game play and involves players from both teams contesting for the ball after it has been thrown in from the side line. Successful lines-out throws require the ball to be delivered accurately to the hands of a jumping and/or lifted team mate (approximately 3-3.5 m off the ground) over distances of between 5- 18 m. Previous research has suggested considerable inter and intra-individual differences in the throwing techniques of international level players. Accordingly, this project investigated the interrelationships between accuracy and the line-out throwing characteristics of three elite international rugby players, and then analyzed whether these changed for throws over increasing length. Three-dimensional (3D) data were developed from video footage (50 Hz) of three elite international subjects for 30 throws over three distances (6 m, 10 m, and 15 m). Results showed notable differences between subjects in many variables at each of the key throw phases. However, several variables such as the degree of trunk flexion at the end of the backswing and at ball release, coupled with elbow flexion angle at ball release remained constant as throw length increased. All subjects exhibited high levels of consistency in movement patterns across all throw lengths. Findings indicated that these high performance line-out throwers shared several common characteristics that will provide useful guides in the development of training programs